Historical roots and environmental impacts of land use in the Luhansk region - Sopov, Dmitry (Human Geography Journal, 2017)
The influence of human activities (particularly agriculture and the coal industry) on the nature of land use in the Luhansk region (separately for right Bank and left Bank parts). The emphasis on the value sarutanont areas and sheet erosion in the degradation of soils and lands, especially on theDonetskridge (the right Bank of the Seversky Donets). The role of prologue reliefDonetskridge as a natural factor in the spread of erosion processes. A brief historical overview of attempts to combat the development of ravines in the Luhansk region that carried out, starting from the second half of the XIX century, but mainly were not effective. As one of the negative factors that influenced the structure of land use, delineated drainage increasing the area under pasture, which increases the intensity of erosion processes.Lighted the detrimental effect of mining activities on the land-use patterns in the study area. Noted regarding the environmental effects of physical exclusion of lands due to their occupation by dumps, waste heaps and other anthropogenic forms of relief, formed mining activities. Emphasized that not only mine, but also the concentrator, communication facilities and the like play a role in the reduction of the area occupied by farmland, and therefore cause negative changes of land use structure in the right-Bank part of the territory of the Luhansk region.Noted that extensive and excessive land use in agriculture and the coal industry in Luhansk region has led to the degradation of large areas of land and the impoverishment of the land fund. Noted that the current structure of land use requires radical changes which should be based on new conceptual principles and a systematic approach to the problems of environmental management.